Clinical characteristics of autoimmune optic neuritis. (January 2017) - Kawachi, Izumi
Abstract: Autoimmune disorders of the central nervous system often involve autoimmune inflammation of the anterior visual pathways. Autoimmune optic neuritis can be categorized as: (i) isolated optic neuritis; (ii) relapsing isolated optic neuritis: (iii) chronic relapsing inflammatory optic neuropathy; (iv) neuromyelitis optica spectrum disorders‐associated optic neuritis; or (v) multiple sclerosis‐associated optic neuritis. Studies of serum‐specific autoantibodies, such as aquaporin‐4 and myelin oligodendrocyte glycoprotein, have revealed some underlying mechanisms of autoimmune optic neuritis. However, the etiology and pathogenesis of most cases of autoimmune optic neuritis remain unclear. The following clinical features of autoimmune optic neuritis are profoundly affected by the unique structure of the human anterior visual pathways: (i) vulnerability to swelling of the intracanalicular optic nerve as a result of the limited space within the bony canal; (ii) inflammatory cell infiltration through the subarachnoid space, pia and pial septa; (iii) compartmentalized dynamics of cerebrospinal fluid as a result of the cul‐de‐sac anatomy of the optic nerve; (iv) permeability of the prelaminar optic nerve head as a result of the lack of classical blood–brain barrier characteristics; and (v) retinal abnormalities, which are a diagnostic window of neurodegenerative processes of the optic nerves and/or brain. Future studies are required to configure a systemic nosology for optic neuritis with international consensus, elucidate specific diagnostic biomarkers, carry out clinical trials of the acute and chronic phases of the disease etiologies, and elucidate possible neuroprotective and remyelinating treatments.